2019
DOI: 10.1021/acsami.9b09010
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene Storage and Separation Using Metal–Organic Frameworks with Open Metal Sites

Abstract: Efficient separation and storage of gas streams involving light hydrocarbons is essential for industrial applications. These hydrocarbons are widely used as energy resources and/or chemical raw materials in various chemical reactions. Here, we focus on the separation of acetylene from methane and carbon dioxide. The separation of acetylene from carbon dioxide is, in particular, challenging due to the similar kinetic diameters and boiling points of the molecules. In recent years, considerable progress has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…[29] It is relatively simple to introduce metal ions into the porphyrin center (Figure 2b), but the disadvantage is that this significantly enhances the effect on C 2 H 4 . [30] It has been shown that C 2 H 6 can be stabilized in the pores through intermolecular dipolar and supramolecular interactions with the aromatic ligands. [31][32][33] Herein, we describe an ew modification, introduction of cyclopentadiene cobalt into the linker based on the stable ftw topology platform (Figure 1b and 2c), together with al ayer of cyclopentadiene wrapped on the outer side of cobalt to selectively increase the force associated with C 2 H 2 and C 2 H 6 .O no ne hand, cyclopentadiene-cobalt can increase the weak interaction with C 2 H 2 and C 2 H 6 and on the other hand, it can further divide the space in the cage to form asphere-like force surface (Figure 2f).…”
Section: Design and Synthesismentioning
confidence: 99%
“…[29] It is relatively simple to introduce metal ions into the porphyrin center (Figure 2b), but the disadvantage is that this significantly enhances the effect on C 2 H 4 . [30] It has been shown that C 2 H 6 can be stabilized in the pores through intermolecular dipolar and supramolecular interactions with the aromatic ligands. [31][32][33] Herein, we describe an ew modification, introduction of cyclopentadiene cobalt into the linker based on the stable ftw topology platform (Figure 1b and 2c), together with al ayer of cyclopentadiene wrapped on the outer side of cobalt to selectively increase the force associated with C 2 H 2 and C 2 H 6 .O no ne hand, cyclopentadiene-cobalt can increase the weak interaction with C 2 H 2 and C 2 H 6 and on the other hand, it can further divide the space in the cage to form asphere-like force surface (Figure 2f).…”
Section: Design and Synthesismentioning
confidence: 99%
“…The traditional modification methods are to expose the metal sites, for example by removal of the coordinated solvent by activation [27, 28] or to directly introduce the metal sites into the linker [29] . It is relatively simple to introduce metal ions into the porphyrin center (Figure 2 b), but the disadvantage is that this significantly enhances the effect on C 2 H 4 [30] . It has been shown that C 2 H 6 can be stabilized in the pores through intermolecular dipolar and supramolecular interactions with the aromatic ligands [31–33] .…”
Section: Resultsmentioning
confidence: 99%
“… 27 , 28 (2) MOF samples are gifted with open metal sites that can strongly interact with guest molecules such as hydrogen and acetylene. 29 33 Therefore, they could potentially be capable of separating gas molecules and sensing neutral and ionic species. However, these materials have many drawbacks, such as low selectivity, complicated synthesis procedures, and limited universality.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Acetylene separation based on metal–organic frameworks with open metal sites. Reprinted with permission from ref ( 29 ). Copyright 2019, American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%